Underwater Work - António Neves Lousada, Sérgio (IntechOpen, 2021)
Underwater work is work done underwater, generally by divers during diving operations. It also includes work done underwater by remotely operated vehicles (ROVs) and manned submersibles. The versatility and multifarious skills of underwater work mean that it is possible to operate over a wide range of activities, working in hyperbaric conditions or in confined spaces. This book exposes and discusses the inner workings of underwater work along with its challenges and opportunities.